1997
DOI: 10.1084/jem.185.12.2043
|View full text |Cite
|
Sign up to set email alerts
|

HLA-A2.1–restricted Education and Cytolytic Activity of CD8+ T Lymphocytes from β2 Microglobulin (β2m) HLA-A2.1 Monochain Transgenic H-2Db β2m Double Knockout Mice

Abstract: Three different HLA-A2.1 monochains were engineered in which either the human or mouse β2-microglobulin (β2m) is covalently linked to the NH2 terminus of the heavy chain by a 15– amino acid long peptide: HHH, entirely human, HHD, with the mouse H-2Db α3, transmembrane, and cytoplasmic domains, and MHD, homologous to HHD but linked to the mouse β2mb. The cell surface expression and immunological capacities of the three monochains were compared with transfected cells, and the selected HHD construct was introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
472
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 453 publications
(483 citation statements)
references
References 42 publications
9
472
0
2
Order By: Relevance
“…We next looked for potential T-cell epitopes of MAGE-A8, utilising the HHD system. It was shown that HHD mice selected the same immunodominant CTL epitopes as recognised by PBL in influenza-infected HLA-A2.1 individuals (Pascolo et al, 1997). Unlike traditional HLA transgenic mice, HHD mice T-cell response is HLA-A2.1 restricted, with no murine background.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We next looked for potential T-cell epitopes of MAGE-A8, utilising the HHD system. It was shown that HHD mice selected the same immunodominant CTL epitopes as recognised by PBL in influenza-infected HLA-A2.1 individuals (Pascolo et al, 1997). Unlike traditional HLA transgenic mice, HHD mice T-cell response is HLA-A2.1 restricted, with no murine background.…”
Section: Discussionmentioning
confidence: 99%
“…The derivation of HLA-A2.1/D b -b2 monochain, transgenic, H-2D b  b2 m double-knockout mice (HHD mice) has been described by Pascolo et al (1997). Mice were bred in the Weizmann Institute of Science (Rehovot, Israel) and maintained and treated according to NIH guidelines.…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation
“…Pathogen-free 8-to 10-week-old female HLA-A2.1 transgenic HHD-1 mice 29 were housed at MannKind Corporation according to IACUC guidelines. All animal studies were reviewed and approved by an IACUC institutional review committee.…”
Section: Mouse Strains and Cell Linesmentioning
confidence: 99%
“…The derivation of HLA-A2.1/D b -b2 monochain, transgenic, H-2D b xb2m double-knockout mice (named HHD mice) has been described by Pascolo et al (1997). CD1-nude mice were bred in the Weizmann Institute of Science (Rehovot, Israel).…”
Section: Micementioning
confidence: 99%